2012
DOI: 10.1128/jvi.06760-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Epstein-Barr Virus Rta DNA Binding

Abstract: The Epstein-Barr virus (EBV) lytic transactivator Rta activates promoters through direct binding to cognate DNA sites termed Rta response elements (RREs). Rta also activates promoters that apparently lack Rta binding sites, notably Zp and Rp. Chromatin immunoprecipitation (ChIP) of endogenous Rta expressed during early replication in B95-8 cells was performed to identify Rta binding sites in the EBV genome. Quantitative PCR (qPCR) analysis showed strong enrichment for known RREs but little or no enrichment for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 78 publications
0
39
1
Order By: Relevance
“…9A). While our experiments to study the capacity of Rta to associate with the distinct regions of oriLyt were in progress, Heilmann et al, using a ChIP-seq approach, reported that the bidirectional BHLF1/BHRF1 promoter that overlaps oriLyt was one of the high-confidence Rta binding sites (49). Our inability to detect an interaction between Rta and the upstream region of oriLyt in the absence or presence of ZEBRA could be attributed either to the lack of such an interaction or to a defect in the ChIP assay used to detect such an interaction.…”
Section: Discussionmentioning
confidence: 99%
“…9A). While our experiments to study the capacity of Rta to associate with the distinct regions of oriLyt were in progress, Heilmann et al, using a ChIP-seq approach, reported that the bidirectional BHLF1/BHRF1 promoter that overlaps oriLyt was one of the high-confidence Rta binding sites (49). Our inability to detect an interaction between Rta and the upstream region of oriLyt in the absence or presence of ZEBRA could be attributed either to the lack of such an interaction or to a defect in the ChIP assay used to detect such an interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Although BRLF1 binds to and activates many of the same early lytic EBV promoters as BZLF1 (33)(34)(35)(36)(37)(38)(39), the effect of DNA methylation on BRLF1-mediated activation has not yet been examined. BRLF1 activates certain lytic promoters (for example, the BRLF1 promoter itself) through indirect mechanisms (40)(41)(42)(43).…”
mentioning
confidence: 99%
“…BRLF1 activates certain lytic promoters (for example, the BRLF1 promoter itself) through indirect mechanisms (40)(41)(42)(43). BRLF1 also directly binds as a homodimer to BRLF1-responsive elements (RREs) contained within many early lytic viral promoters, with a consensus sequence of GNCCN 9 GGNG (in which N 9 is a spacer sequence that can be any nucleotide) (33)(34)(35)(36)(37)(38)(39). Interestingly, a number of previously confirmed RREs contain CpG motifs, suggesting that DNA methylation may affect the ability of BRLF1 to bind to and/or activate lytic viral promoters.…”
mentioning
confidence: 99%
“…After binding to Rta-responsive elements (RREs), Rta activates viral lytic genes (Chevallier-Greco et al, 1989;Heilmann et al, 2012;Kenney et al, 1989;Quinlivan et al, 1993), and is known to form a complex with Sp1 through MCAF1 to autoregulate the BRLF1 promoter (Rp) and enhance Sp1-dependent transcription (Chang et al, 2005). Moreover, Rta can activate phosphorylation of the p38, JNK and ERK signalling pathways (Adamson et al, 2000;Lee et al, 2008) to induce binding of an Rta-MCAF1-phosphorylated ATF2 protein complex with the ZII element in Zp, thus activating Zta expression (Adamson et al, 2000;Lin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%